A Development of E-Learning Chemistry Based on Project Based Learning on Buffer Solution Using Then Flipped Classroom Approach in Class XI SMA/MA - Aroma Karmila; Nor Adila Rosli Arief; Shintia Friska; Leli Astuti (Center For Advanced Material Processing, Artificial Intelligence, Biophys-Informatics (CAMPBIOTICS), Universitas Negeri Padang, 2022)
Abstract—This development research aims to produce a development product in the form of E learning based on Project Based Learning (PPA) with a valid Flipped Classroom approach in SMA / MA. This study uses a 4-D model development research design which includes defining, designing, developing and distributing. The product validity test was carried out by collecting data from three validators (high school chemistry teachers) using an instrument in the form of a validation questionnaire. Based on the qualitative descriptive analysis using the formula